Pengaman Pintu Rumah Berbasis Sensor Sidik Jari Dan Magnetic Sensor - Ade Septryanti; Erlangga Satria Permana (Universitas Negeri Medan, 2020)
The house has one important part, the door, where the door is the main access to the occupants of the house. The door has a key when wanting to open it, to open a door sometimes the house key is vulnerable to being broken, duplicated or even lost. The use of fingerprint sensors on the door can help homeowners avoid theft, which is when it is not in accordance with the identity of the residents of the GSM 900 SIM will send an SMS notification and a buzzer as an alarm will sound. Prototype models include the stages of gathering needs, building prototypes, evaluating, coding the system, testing the system, evaluating the system and using the system. Fingerprint sensor has been tested and can be used on residents to support security at the door.